2019
DOI: 10.1111/are.14198
|View full text |Cite
|
Sign up to set email alerts
|

Differences in metabolism of triploid and diploidSalmo trutta f. lacustrisunder acclimation conditions and after exposure to stress situations

Abstract: Differences in metabolism (enzyme activities, metabolites) between diploid and triploid Salmo trutta f. lacustris were investigated under acclimation and stress conditions. Under acclimation conditions enzyme activities differed for 35% of the 27 investigated key regulatory enzymes and temperature optima for 23%. Muscle and liver metabolites related to energy metabolism and diagnostic indices of blood serum were similar, with exception of acetyl‐CoA being increased in triploids. Metabolic rate was lower and gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As predicted, interspecific analyses often show that mass-specific metabolic rate is negatively related to genome size [ 8 , 118 , 205 , 238 , 253 , 256 , 257 , 320 , 325 , 326 , 327 , 328 , 329 ] (but see [ 330 ]). However, intraspecific tests in animals comparing polyploids with diploids have shown that increasing ploidy more often has no effect on metabolic rate than negative effects, and sometimes positive effects have even been observed (reviewed in [ 331 , 332 , 333 , 334 ]; also see [ 335 , 336 ]), as also seen for rates of photosynthesis in plants (e.g., [ 195 , 201 , 293 , 333 ]). Differences in metabolic rate between polypoid and diploid animals may be temperature-dependent [ 334 , 335 , 336 ].…”
Section: Discussionmentioning
confidence: 99%
“…As predicted, interspecific analyses often show that mass-specific metabolic rate is negatively related to genome size [ 8 , 118 , 205 , 238 , 253 , 256 , 257 , 320 , 325 , 326 , 327 , 328 , 329 ] (but see [ 330 ]). However, intraspecific tests in animals comparing polyploids with diploids have shown that increasing ploidy more often has no effect on metabolic rate than negative effects, and sometimes positive effects have even been observed (reviewed in [ 331 , 332 , 333 , 334 ]; also see [ 335 , 336 ]), as also seen for rates of photosynthesis in plants (e.g., [ 195 , 201 , 293 , 333 ]). Differences in metabolic rate between polypoid and diploid animals may be temperature-dependent [ 334 , 335 , 336 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like interspecific comparisons, intraspecific comparisons of R / M with cell size often show significant negative relationships [ 33 , 39 , 55 , 58 , 59 , 60 , 61 , 62 , 63 ], but contrary to cell SA theory, nonsignificant [ 39 , 61 , 64 , 65 , 66 , 67 ] and even positive [ 42 , 56 , 59 , 60 , 63 , 68 ] relationships have also been frequently reported. Why intraspecific relationships vary so much is little understood, but differences in temperature [ 28 , 54 , 59 , 61 , 63 ], fasting duration [ 68 ], developmental stage [ 39 ], tissue type [ 40 , 60 ], and duration of laboratory acclimation [ 61 , 63 ] or evolutionary adaptation [ 54 , 56 , 69 ] may be at least partially involved.…”
Section: Major Ways That Variation In Metabolic Rate May Relate To Ce...mentioning
confidence: 99%
“…Triploidization affected activities of main regulatory enzymes in S . trutta (Lahnsteiner et al ., 2019) and O . mykiss (Babaheydari et al ., 2017).…”
Section: Discussionmentioning
confidence: 97%
“…fontinalis – Stillwell & Benfey, 1996, S . trutta – Lahnsteiner et al ., 2019) and stress response ( S . fontinalis – Hyndman et al ., 2003, Atlantic salmon S .…”
Section: Discussionmentioning
confidence: 99%